RETRACTED ARTICLE: Treatment of temporomandibular joint internal derangement using MESNA injection - Ahmed A. Mosleh (BMC Oral Health)
Abstract Introduction The development of temporomandibular disorders specifically emphasizes the biochemical changes occurring in the synovial fluid at different stages of temporomandibular joint disease. Research has indicated that inflammation may be a primary reason behind the pain and dysfunction in temporomandibular joint diseases. Since its clearance several years ago, MESNA (sodium 2-mercaptoethanesulfonate) has been used in various formulations as a mucolytic drug in the respiratory domain. It operates by disrupting the disulfide bonds present between polypeptide chains within mucus. MESNA exhibits minimal tissue distribution, with the material being swiftly and thoroughly eliminated via the kidneys. Objectives To assess the efficacy of injecting MESNA directly into the Temporomandibular Joint to treat internal derangement. Materials and methods A randomized clinical trial was conducted on sixty patients who exhibited non-responsiveness to conventional treatment and were diagnosed with TMJ anterior disc displacement with reduction. The patients were chosen from the outpatient clinic of the Oral and Maxillofacial Surgery Department at Tanta University Faculty of Dentistry. Two equal groups of patients were randomly assigned to each other. Group I (Mesna group) received intra-articular injection with MESNA solution. Group II (Standard group) received arthrocentesis with lactated ringer solution followed by injection of Hyaluronic Acid (HA). The data was gathered by functional examinations such as maximum interincisal opening (MIO) and clicking. A Visual Analogue Scale (VAS) assessed pain severity before and after treatments. Results Both MESNA and HA showed significant improvement up to six months of the follow-up compared to preoperative status, as evidenced by better mouth opening, lateral excursion, lower clicking, and reduced pain score in patients with TMDs. MESNA showed significant improvement during follow-up compared to HA. Conclusion Compared to HA, MESNA showed a more noticeable improvement during the follow-up period.